Soil organic carbon stocks in the blue carbon habitats of Bangladesh - Uddin, Md Jashim; Rahman, Arafat; Kibria, ASM Mahbub E; Ali, AHM Zulfiquar (Dhaka University Journal of Biological Sciences, 2023)
A study was conducted in the coastal blue carbon habitats of Bangladesh regarding soil organic carbon (SOC) stocks. Fifty soil samples covering 10 soil profiles at five different depths level up to 1 m was considered to complete the above research. In the salt marsh sites, SOC ranged from 13.1 to 45.7 g/kg with a mean value of 27.5 g/kg. In the mangrove sites, SOC varied from 14.1 to 46.3 g/kg with a mean value 26.4 g/kg. In Mangrove ecosystem soils, clay contents showed a very strong positive correlation with SOC (r = 0.901 and p < 0.01) whereas silt showed a significant positive correlation with the SOC (r = 0.691 and p< 0.05) in the salt marsh sites. As the mangrove ecosystem holds more clay than the salt marsh ecosystem so it may be said that mangrove soils are more potential for carbon storage than salt marsh soils. The study revealed that both of these ecosystems hold more carbon than the threshold level (20.0 g/kg). It is suggested to protect and regenerate the blue carbon habitats in the coastal ecosystem considering the present findings to tackle climate change and other sudden disasters. Dhaka Univ. J. Biol. Sci. 32(2): 179-188, 2023 (July)